Introducing a computer feeding system at various lactational stages for dairy cows - J.C. Kube; John E. Shirley; K.D. Frantz; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1986)
Lactating dairy cows were introduced to a computer feeder in early (≤120 days in milk or D.I.M.), mid (120-220 D.I.M.), and late (>220 D.I.M.) lactation. Cows in the mid- and late-lactation groups adjusted quicker and exhibited a smaller decrease in production, relative to the early lactation group. Computer-controlled feeders are increasing in popularity nationwide and are creating some interest among dairy producers in the midwest. Computer-controlled feeders allow dairy producers with small to medium-sized herds to feed their cows according to production without dividing cows into groups or dispensing feed in the parlor. Many times, a producer considers only the cost of purchasing the computer feeder, but should realize that there is an additional expense involved in adjusting the cows to the feeder. This trial was designed to establish some guidelines as to when to introduce cows to a computer feeder, while holding production as close to normal as possible.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Lactation; Computer feeder; Milk traits